Retrospective Cohort Study of Lassa Fever in Pregnancy, Southern Nigeria - Sylvanus Okogbenin; Joseph Okoeguale; George Akpede; Andres Colubri; Kayla G. Barnes; Samar Mehta; Reuben Eifediyi; Felix Okogbo; Joseph Eigbefoh; Mojeed Momoh; Mojeed Rafiu; Donatus Adomeh; et al. (Emerging Infectious Diseases, 2019)
Lassa fever in pregnancy causes high rates of maternal and fetal death, but limited data are available to guide clinicians. We retrospectively studied 30 pregnant Lassa fever patients treated with early ribavirin therapy and a conservative obstetric approach at a teaching hospital in southern Nigeria during January 2009–March 2018. Eleven (36.7%) of 30 women died, and 20/31 (64.5%) pregnancies ended in fetal or perinatal loss. On initial evaluation, 17/30 (56.6%) women had a dead fetus; 10/17 (58.8%) of these patients died, compared with 1/13 (7.7%) of women with a live fetus. Extravaginal bleeding, convulsions, and oliguria each were independently associated with maternal and fetal or perinatal death, whereas seeking care in the third trimester was not. For women with a live fetus at initial evaluation, the positive outcomes observed contrast with previous reports, and they support a conservative approach to obstetric management of Lassa fever in pregnancy in Nigeria.